VD_FINDINFO ML / 2015 / 48 vom 5. März 2015 - VD Tribunal cantonal (2015)
MAINLEVÉE PROVISOIRE, RECONNAISSANCE DE DETTE, COMPENSATION DE CRÉANCES | 120 al. 1 CO, 120 al. 2 CO, 120 CO, 82 al. 1 LP, 82 LP